General Geology of the Semanggol Formation in Bukit Kukus, Kedah with Emphasis on Deformation within Lower Chert Member - Azahari, Norfahira Najeehah (2016)
This research will discuss the structural deformation of chert unit in Semanggol Formation at Bukit Kukus. The outcrop has an area of 30 m² and is located approximately 5 km from Kuala Ketil. There are six lithofacies that have been identified in Bukit Kukus, Kuala Ketil, Kedah which are mudstone, interbedded chert with mudstone, interbedded sandstone and mudstone, chert, interbedded chert and sandstone and siliceous shale. The depositional environment of these chert sequence is deep marine environment below CCD level because no calcareous material has been observed. The maximum stress that cause the deformation of the chert in the outcrop is from the direction NW-SE with range value of 300° to 305°. In relation to the lineament analysis, the maximum stress direction is almost similar which are in the direction of NW-SE with range in value of 306° until 310°. The fault observed in is a strike-slip dextral fault which is an antithetic fault in relation to Bok Bak fault which is a sinistral fault. The regional analysis shows that the deformation in the regional scale may have caused the most recent deformation of chert within the study area.